Assessment of chamber angle pigmentation during longterm latanoprost treatment for open‐angle glaucoma - Nakamura, Yuko; Nakamura, Yoshimi; Morine‐Shinjo, Sayo; Sakai, Hiroshi; Sawaguchi, Shoichi (Acta Ophthalmologica Scandinavica, 2004)
. Purpose:  This study aimed to determine whether the longterm use of latanoprost is associated with an increase in trabecular pigmentation, especially in subjects in whom iris pigmentation has increased. Methods:  We enrolled 50 subjects for whom treatment was to start for ocular hypertension, primary open‐angle glaucoma or normal tension glaucoma. All subjects received latanoprost 0.005% daily. Trabecular pigmentation was documented using gonioscopic photography of the inferior quadrant at baseline, every 3 months for the first year and every 6 months for the second and third years. Three glaucoma specialists evaluated the series of gonioscopic photographs for each eye of each subject in a masked fashion. The intraocular pressure (IOP) was also recorded at each visit. Results:  A total of 41 subjects (79 eyes) completed 3 years of follow‐up, and none showed any increase in the grade of trabecular pigmentation, including 10 subjects (20 eyes) in whom the iridial pigment increased. Conclusion:  Although latanoprost increased iridial pigmentation in some subjects, we found no evidence of an increase in trabecular pigmentation over the 3 years of follow‐up.